Pengaruh Online Customer Review Dan Tagline “Gratis Ongkir” Terhadap Keputusan Pembelian - Stiffanny, Nichollin; Adlina, Hafiza (Jurnal Ilmiah Wahana Pendidikan, 2025)
In this digital era, the development of internet technology has greatly influenced people's lifestyles, especially in shopping which nowadays can easily be done online. Shopee is an e-commerce company that continues to grow and compete to maintain its position in the hearts of the public. Therefore, Shopee needs the right strategy to attract consumer interest and loyalty. This research aims to analyze the influence of online customer reviews and the tagline "Gratis Ongkir" on purchase decision among Generation Z Shopee users in Medan City. The influence between online customer reviews and the tagline "Gratis Ongkir" will be analyzed partially and simultaneously. This research uses quantitative methods with an associative approach. The population in this study are Generation Z Shopee users in Medan City with a sample of 96 respondents. Sampling was carried out using non-probability sampling and by using purposive sampling technique. The data collection method in this research is using primary data obtained by distributing questionnaires and secondary data obtained through literature study. The analytical methods used are validity testing, reliability testing, classical assumption testing, multiple linear regression analysis and hypothesis testing. The results of this research show that the online customer review (X1) and tagline (X2) variables have a significant partial and simultaneous effect on purchase decision (Y). The correlation coefficient (R) value shows that there is a close relationship between online customer reviews (X1) and taglines (X2) on purchase decision (Y), namely 0.741. The Adjusted R Square value obtained is 0.550, which means that the online customer review (X1) and tagline (X2) variables contribute to purchase decision (Y) by 55%, while the remaining 45% is the contribution from other variables or factors not included in this research.